Analisis Implementasi Pembelajaran Diferensiasi pada Kurikulum Merdeka Kelas II di Sekolah Penggerak Kecamatan Jetis - Kinanthi, Eka Wahyu; Apriani, An-Nisa; Suryandari, Suryandari; Ismanto, Ismanto (Alma Ata University Press, 2025)
Differentiated learning is student-centered learning and aims to meet students' learning needs. This research aims to determine the implementation, impact, advantages and disadvantages of differentiated learning. This type of research uses descriptive qualitative research. Data collection was carried out by observation, interviews, questionnaires, and documentation. It can be seen from how Differentiated Learning is implemented in the Merdeka Curriculum at the Driving School, Kec. Jetis, Bantul Regency includes SD Negeri 1 Sumberagung, SD Negeri Jetis, and SD Muhammadiyah Blawong 1. The data sources consist of 3 school principals, 3 class II teachers and class II students totaling 73 students and less than 100, so this population can be used as a research sample. The results of the research show that the implementation of differentiated learning in class II at the Jetis District Driving School has been running optimally. However, there is one driving school that has not been optimal, namely SD Muhammadiyah Blawong 1. The implementation of differentiated learning goes through several stages, namely planning, implementation and evaluation. Differentiated learning planning is carried out by school principals, namely educators, managers and learning supervisors. Teachers carry out differentiated learning by applying differentiated learning components. Learning evaluation is carried out using diagnostic formative and summative assessments. The impact on differentiated learning can be seen and measured using a Likert scale with a percentage result 100 % from numbers 1-4 in the Likert scale categories.The advantages and disadvantages are almost the same as the implementation conditions, where there are two schools that are optimal and there is one driving school that is not yet optimal because of supervision so they have to bring in a supervisor. And it can be calculated using a Likert scale from statements made by researchers and has positive results, namely 97%.Keyword: Implementation, Impact, Strengths and Weaknesses of Differentiated Learning, Grade II Elementary School, Independent Curriculum, Driving School